High‐Fidelity Numerical Study of the Effect of Wing Dam Fields on Flood Stage in Rivers - Xun Han; Gary Parker; Pengzhi Lin (Water Resources Research)
Abstract Trains of wing dams (spur dikes) are used in river engineering for navigation in many rivers, such as the Mississippi River. These structures increase water level due to added resistance, and thus increase flood stage. The redistribution of bed sediment associated with constriction scour in the central channel zone and deposition along the banks between wing dams, however, may result in a compensating decrease in water stage. The net effect of wing dams on flood stage is determined by a balance between these two effects. We apply a high‐fidelity 3D numerical model (LES rather than RANS or shallow water approach) to investigate the flow, water level and sediment transport in wing dam fields. We study both fully emergent (tops of wing dams protrude above water surface) and submerged (tops of wing dams below water surface) fields. Our results for a simplified configuration show that (a) the additional resistance of wing dams does indeed increase water stage, but (b) much of this increase is reduced via in‐channel redistribution of bed sediment, including non‐local contraction scour in the main channel. In all cases studied here, when the bed is fully erodible, wing dams increase depth in the central channel region between the wing dam field, promoting navigability there. We provide a direct upscale our results to an Upper Reach of the Lower Mississippi River (URLMR) using distorted Froude scaling, but outline numerous caveats which motivate future studies.